PENGARUH DOSIS PUPUK UREA DAN FREKUENSI PENYIRAMAN TERHADAP PERTUMBUHAN SETEKNILAM ACEH (Pogostemon cablin Benth) - Erida Nurahmi; Taufan Hidayat; Mishar Mishar (Jurnal Floratek, 2017)
The purpose of this study was to determine the dose of urea fertilizer and proper watering frequency on the growth of patchouli cuttings Aceh and whether there is interaction between the two factors. Factors urea fertilizer consists of 3 levels: 1 g/polybag, 2 g/polybag and 3 g/polybag. Watering frequency factor also consists of 3 levels: 2 times a day, 1 time a day and 2 days of watering.The results showed a significant effect of urea fertilizer on plant height at 15 DAP, however no significant effect on plant height age of 30, 45 and 60 DAT, the number and percentage of shoots grown at 15, 30, 45 and 60 DAP. Patchouli better growth obtained in the treatment of urea fertilizer dose of 2 g / polybag. The frequency of watering did not significantly affect plant height, number of shoots, a growing percentage of the age of 15, 30, 45 and 60 DAP. Better growth likely to be obtained at the frequency of watering treatment 1 a day.There is no real interaction between the dose of urea with the frequency of watering on plant height, number of shoots and the percentage is growing at 15, 30, 45 and 60 DAP.